Joint marketing and community empowerment: a study of family farmers in Santiago del Estero (Argentina) - Jara, Cristian Emanuel (2025)
This article examines how joint marketing initiatives can contribute to processes of community empowerment. In this regard, we analyzed the conditions that enable breaking away from disempowerment, recognizing agency capacity, and achieving collective gains through organization. Based on a case study of family farmers who partnered to sell their products, five key dimensions were identified, illustrating how this associative sales strategy can significantly expand producers’ margins of autonomy. The role of endogenous resources, diversification, the activation of territorial synergies, the adoption of sustainability criteria, and the design of solidarity-based institutional frameworks are highlighted. This type of study not only has the potential to enrich rural social studies but also provides valuable guidance for strengthening innovative models of emerging rural development in Latin America.